IMPLEMENTASI MODEL ATIK UNTUK MENINGKATKAN KECERDASAN KINESTETIK MELALUI KEGIATAN MENARI TARIAN BAKIAK: IMPLEMENTATION OF THE ATIK MODEL TO IMPROVE KINESTHETIC INTELLIGENCE THROUGH BAKIAK DANCE ACTIVITIES - WIDARTI EMILIANA; DEBORA PUJO; SRI WATINI (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
For Upgrade ability child in observing, imitating and could do movement for could Upgrade intelligence kinesthetic with do movement dance Clogs that is aim from study the development of the ATIK model. Observational child _ in study this there are 17 children . And the technique used with observation and interview . Then Technique processing of this data is with descriptive that is tell whole condition child . First thing to do is observing children in TK Strada Bina Sejahtera who have good development _ like develop very good (BSB) of whole child . kindly gradually observation done in a manner continuous so could generate authentic data . Development child could seen moment they do movement dance with method observing , imitating then do movement in accordance with rhythm music . With do activity dance Clogs could stimulate ability intelligence kinesthetic child .